THE RESULTS OF THE XVI ALL-RUSSIAN CONGRESS “HYPERTENSION 2020: SCIENCE IN THE SERVICE OF PRACTICAL HEALTH CARE”, MARCH 11-12, 2020 IN YAROSLAVL - Article Editorial (Евразийский Кардиологический Журнал, 2020)
The results of the XVI All-Russian Congress “Hypertension 2020: science in the service of practical health care”, March 11-12, 2020 in Yaroslavl.